Low-Frequency Movements in Stock Prices: A State-Space Decomposition - Balke, Nathan S.; Wohar, Mark E. (The Review of Economics and Statistics, 2002)
Previous analyses have concluded that expectations of future excess stock returns rather than future real dividend growth or real interest rates are responsible for most of the volatility in stock prices. In this paper, we employ a state-space model to model the dynamics of the log price-dividend ratio along with long-term and short-term interest rates, real dividend growth, and inflation. The advantage of the state-space approach is that we can parsimoniously model the low-frequency movements present in the data. We find that, if one allows permanent changes, even though very small, in real dividend growth, real interest rates, and inflation-but not excess stock returns-then expectations of real dividend growth and real interest rates become significant contributors to fluctuations in stock prices. However, we also show that stock price decompositions are very sensitive to assumptions about which unobserved market fundamentals have a permanent component. When we allow excess stock returns to have a permanent component but not real dividend growth, excess stock returns become an important contributor to stock price movements, whereas real dividend growth does not. Unfortunately, the data is not particularly informative about which of these alternative models is more likely.